Harmonisation of national criminal laws on maritime piracy: a regulatory proposal for the crime of piracy and its penalties - López Lorca, Beatriz (European journal on criminal policy and research, 2017)
This article outlines a regulatory proposal for the crime of piracy and its penalties. Following the introduction, Section 2 addresses the duty to cooperate in the repression of maritime piracy established in Article 100 of the United Nations Convention on the Law of the Sea (UNCLOS). It also discusses the existence of an obligation to codify the crime of piracy and establish appropriate penalties, as part of the duty under Article 100. In this context, Section 4 is a de lege lata analysis of how national legislators have codified maritime piracy while Section 5 is a de lege ferenda proposal. Namely, Section 4 identifies some regulatory patterns in a wide number of jurisdictions that show to what extent there is a lack of harmonisation of domestic laws on maritime piracy. Section 5 discusses a regulatory proposal for the crime of piracy and its penalties.